PENDAMPINGAN DESAIN KEMASAN WAJIK TAPAI MELAYU RIAU UNTUK MENINGKATKAN PENDAPATAN - Maryanti, Sri; Sudiar, Nining; Suci, Afred; Hardi, Hardi (Universitas Muhammadiyah Tapanuli Selatan, 2021)
This goal is to redesign the packaging for wajik tapai melayu that keep up with the times without changing the logo and product names that were previously known, redesigning the packaging for wajik tapai melayu with more practical steps and calculating the performance of products and packaging for wajik tapai melayu. The method used is to coordinate with partners, assistance by providing views to partners about the redesign of the packaging for wajik tapai melayu and conducting market trials with new packaging from wajik tapai melayu by observing consumer responses related to changes in wajik tapai melayu packaging by going down to the shop where the product is marketed. The results show that 24 months before community service activities began, the average sales of new wajik tapai melayu were around Rp. 67 million per month after the partner's average income was Rp. 114 million per month or an increase of 69.4%. Then the increase in income with the result of an increase of 16.3% on average to IDR 132 million per month. From the p-value .000 *** it can be ignored that the average increase that occurs is significant. That is, offering care and rejuvenation packaging that can significantly increase income for community service partners. The packaging comparison test results show that consumers agree to this contract and significant changes in graphic design and packaging form. Meanwhile, in terms of information on the packaging, there was relatively no significant difference (p-value = .159) between the old packaging and the new package. This is because there is not much information added or given from the two packages, so that the type of information presented is relatively the same by consumers.